Split resonance modes of a AuBRC plasmonic nanosystem caused by the coupling effect. (14th November 2016) - Ni, Yuan; Kan, Caixia; Xu, Haiying; Wang, Changshun
Abstract: A plasmonic nanosystem can give rise to particular optical responses due to a coupling effect. In this work, we investigate the optical properties and field distributions of a novel 'matrioska' nanocavity structure composed of a Au nanorod (AuNR) within a nanobox (AuNB) via finite-difference time-domain (FDTD) simulation. This nanocavity can be fabricated by a two-step wet-chemical method. The multiple SPR modes of optical spectrum for nanocavity are caused by the strong interaction between the AuNR-core and AuNB-shell when the incident light is perpendicular or parallel to the long axis of the Au box/rod nanocavity (AuBRC). The SPR modes are known as the dipole–dipole bonding resonance mode in the lower-energy region and the antibonding resonance mode in the higher-energy region. It is proposed that AuBRC can escape the orientation confinement of AuNR because the multiple modes occur and provide a potential application for the enhancement of the photoluminescence signal. Additionally, the SPR modes red-shift with increasing the offset of the AuNR-core, whereas the SPR mode dramatically blue-shifts when the conductive coupling is formed. The intense 'hot-spot' could be induced within a small interaction region in the conductive coupled system. The SPR line-shape of high quality would also be promoted. The SPR is highly sensitive to the medium, which is promising in the sensing and detecting devices.